Neighborhood Disadvantage, Racial Concentration and the Birthweight of Infants born to Adolescent Mothers - Madkour, Aubrey Spriggs (2014)
OBJECTIVE: To study the relationship between neighborhood demographic characteristics (disadvantage, racial concentration) and the birthweight of infants born to adolescent mothers, potentially as mediated by smoking, prenatal care use, or perceptions of neighborhood safety. METHODS: Data from Waves I and IV of the National Longitudinal Survey of Adolescent Health were analyzed. Birthweight (continuous) and low birthweight (<2.5 kg) of singleton infants born to non-Hispanic Black and non-Hispanic White adolescent mothers (<20 years) after Wave I were examined as outcomes. Neighborhood demographic characteristics included Census Block Group socioeconomic disadvantage and Black racial concentration. Possible mediators (smoking during pregnancy, early initiation of prenatal care, and perceptions of safety) were also examined. Controls for adolescent baseline age, age at pregnancy, body mass index (BMI) and parental education were included. Analyses were run stratified on race. RESULTS: Baseline continuous birthweight, BMI and neighborhood demographics varied significantly between non-Hispanic Black and White adolescent mothers, with Black adolescent mothers evidencing lower birthweight and higher BMI, neighborhood disadvantage and Black racial concentration. In multivariable analyses among Black adolescent mothers, Black racial concentration was positively associated with birthweight, and negatively associated with low birthweight; no mediators were supported. Neighborhood disadvantage and Black racial concentration were unassociated with birthweight outcomes among White adolescent mothers. CONCLUSIONS: Infants born to Black adolescent mothers evidenced higher birthweight with increasing Black neighborhood concentration. Further exploration of mechanisms by which Black racial concentration may positively impact birthweight is warranted.